Cardiopulmonary Exercise Testing Suggests a Beneficial Response to Pulmonary Endarterectomy in a Patient with Chronic Thromboembolic Obstruction and Normal Preoperative Pulmonary Hemodynamics. (1st March 2014) - McCabe, Colm; Preston, Stephen D.; Gopalan, Deepa; Dunning, John; Pepke‐Zaba, Joanna
Abstract : Pulmonary endarterectomy offers a symptomatic and survival benefit in patients with chronic thromboembolic pulmonary hypertension through sustained improvement in right ventricular function. However, its role in patients with symptom limitation, chronic thrombotic obstruction, and a normal pulmonary hemodynamic profile is less clear. Cardiopulmonary exercise testing (CPET) stresses the cardiopulmonary system and has a characteristic response in pulmonary hypertension. CPET may therefore reveal abnormalities in patients with chronic thrombotic obstruction where hemodynamic investigations conducted at rest are reassuring. Using incremental CPET, we demonstrated improvements in right ventricular performance and ventilatory efficiency following pulmonary endarterecomy in a patient with preoperative exercise limitation and normal pulmonary hemodynamics. Careful evaluation of exercise responses may extend the potential benefit offered by pulmonary endarterectomy in patients with chronic thromboembolic obstruction irrespective of their resting hemodynamic profile.